What can motivate Lady Health Workers in Pakistan to engage more actively in tuberculosis case-finding? - Mishal S. Khan; Nelofar Mehboob; Afifah Rahman-Shepherd; Farah Naureen; Aamna Rashid; Naveed Buzdar; Muhammad Ishaq (BMC, 2019)
Abstract Background Many interventions to motivate community health workers to perform better rely on financial incentives, even though it is not clear that monetary gain is the main motivational driver. In Pakistan, Lady Health Workers (LHW) are responsible for delivering community level primary healthcare, focusing on rural and urban slum populations. There is interest in introducing large-scale interventions to motivate LHW to be more actively involved in improving tuberculosis case-finding, which is low in Pakistan. Methods Our study investigated how to most effectively motivate LHW to engage more actively in tuberculosis case-finding. The study was embedded within a pilot intervention that provided financial and other incentives to LHW who refer the highest number of tuberculosis cases in three districts in Sindh province. We conducted semi-structured interviews with 20 LHW and 12 health programme managers and analysed these using a framework categorising internal and external sources of motivation. Results Internal drivers of motivation, such as religious rewards and social recognition, were salient in our study setting. While monetary gain was identified as a motivator by all interviewees, programme managers expressed concerns about financial sustainability, and LHW indicated that financial incentives were less important than other sources of motivation. LHW emphasised that they typically used financial incentives provided to cover patient transport costs to health facilities, and therefore financial incentives were usually not perceived as rewards for their performance. Conclusions This study indicated that interventions in addition to, or instead of, financial incentives could be used to increase LHW engagement in tuberculosis case-finding. Our finding about the strong role of internal motivation (intrinsic, religious) in Pakistan suggests that developing context-specific strategies that tap into internal motivation could allow infectious disease control programmes to improve engagement of community health workers without being dependent on funding for financial incentives.